Konsep Negara Hukum dan Demokrasi dalam Pandangan Abdul Qahhar Mudzakkar - Abbas, Abbas (Amsir Law Journal, 2021)
The research aims to find out about the conception of the state of law and democracy aspired by Abdul Qahhar Mudzakkar. The type of research used in this study is the socio-juridical type of research. Juridically because the unit of analysis in this research is an idea, the idea knows the concept. Where in what is meant is an idea Abdul Qahhar Mudzakkar about the concept of a state of law and democracy. Empirically the author sought to see the historical facts about the application of the concept correlated with the constitution of the Republic of Indonesia in the era of President Soekarno’s leadership. The results showed Abdul Qahhar Mudzakkar wanted the Indonesian state as an Islamic state with a presidential system of government while still carrying out the principles of true democracy. True democracy means Abdul Qahhar Mudzakkar is a tribute to the values of martyrdom, pluralism, and justice. This certainly requires better time, methods, and refinements if you want to be applied in a plural Indonesia.